DNA interstrand cross-link repair in the cell cycle: a critical role for polymerase zeta in G1 phase. - McHugh, P; Sarkar, S (2006)
DNA interstrand cross-links (ICLs) present a formidable challenge to the cellular repair apparatus, but to date ICL repair pathways have proved difficult to dissect genetically. It now appears that this is partly the result of a high degree of cell cycle phase selectivity in the choice of ICL pathway employed. Here we review recent results showing that Polymerase zeta, specialized translesion plays an important role during ICL repair in G1 phase yeast cells, and that PCNA modification by ubiquitin is a key regulator of its activity. Given that this reaction can occur outside the context of S-phase, these results imply a more general role for PCNA modification in the control of DNA repair pathways through the cell cycle, which is dependent on the type of damage or repair intermediate encountered.